2009
DOI: 10.1001/archfacial.2009.30
|View full text |Cite
|
Sign up to set email alerts
|

Profilometric and Morphometric Response of Murine Skin to Cosmeceutical Agents

Abstract: The pronounced effects noted with all 3 compounds indicate that topical agents other than retinoic acid may have comparative stimulating effects on the skin in nonirradiated mice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 30 publications
0
9
0
Order By: Relevance
“…For example, a similar protocol applying retinoid at a higher dosage (0.1%) in human skin led to a slow and gradual increase in collagen 14 . Contrarily, RA has been described as a potent and rapid stimulator of collagen in photoaged human skin, 3 however in mice, application of RA 0.05% for 2 weeks was sufficient to reduce wrinkles 7 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, a similar protocol applying retinoid at a higher dosage (0.1%) in human skin led to a slow and gradual increase in collagen 14 . Contrarily, RA has been described as a potent and rapid stimulator of collagen in photoaged human skin, 3 however in mice, application of RA 0.05% for 2 weeks was sufficient to reduce wrinkles 7 …”
Section: Discussionmentioning
confidence: 99%
“…Retinoids can also influence DNA repair and gene expression to increase ECM production 6 . Application of RA 0.05% for 2 weeks promoted wrinkle reduction in rats 7 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, skin epidermis in vitamin A‐deficient rats is thinner as compared with control rats (35,36). In contrast, RA‐treated skins show an increase in epidermal thickness by hyperplasias of stratum spinosum as compared with control skins (25,27,32,37). In the current study, we showed that type 1 diabetic rats are vitamin A‐deficient.…”
Section: Discussionmentioning
confidence: 91%
“…Morphometry was performed to obtain the following data: (1) epidermal width; (2) total dermal width; (3) ratio of collagen layer to total dermis; (4) ratio of collagen I: collagen III from Herovici polychrome stain preparation (red and blue fibers); (5) count of mast cells; (6) intersection pointcounting to determine fractional area of elastic fibers; 14 and (7) count of PCNA-positive cells to determine epidermal proliferation index. 15,16 Quantitative results are expressed as means¡ standard deviation, and differences between mean scores were analyzed by non-parametric KruskalWallis k-sample test using SPSS16.0 and Excel softwares.…”
Section: Methodsmentioning
confidence: 99%